2018
DOI: 10.1016/j.vetmic.2018.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Detection of foot-and-mouth disease virus in milk samples by real-time reverse transcription polymerase chain reaction: Optimisation and evaluation of a high-throughput screening method with potential for disease surveillance

Abstract: HighlightsFMDV was detected by rRT-PCR in milk up to 28 days post contact challenge.FMDV was detected in milk collected from infected farms in the field (UK 2007).FMDV detection was possible when a milk sample was diluted up to 10−7 in negative milk.Pooled milk has the potential to be a valuable sample type for FMDV surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 31 publications
5
19
0
Order By: Relevance
“…This could be due to poor farmer recognition of clinical signs, lack of disease reporting, or sample contamination (as discussed above). Alternatively, these results may indicate that FMDV can be detected in milk samples during the pre‐clinical or convalescence phases of infection, as reported previously (Armson et al., ; Blackwell & McKercher, ; Reid et al., ), or even during subclinical infection.…”
Section: Fmdv Detection In Milk Samples and Epithelial Samplessupporting
confidence: 76%
See 3 more Smart Citations
“…This could be due to poor farmer recognition of clinical signs, lack of disease reporting, or sample contamination (as discussed above). Alternatively, these results may indicate that FMDV can be detected in milk samples during the pre‐clinical or convalescence phases of infection, as reported previously (Armson et al., ; Blackwell & McKercher, ; Reid et al., ), or even during subclinical infection.…”
Section: Fmdv Detection In Milk Samples and Epithelial Samplessupporting
confidence: 76%
“…Alternatively, these results may indicate that FMDV can be detected in milk samples during the pre-clinical or convalescence phases of infection, as reported previously (Armson et al, 2018;Blackwell & McKercher, 1982;Reid et al, 2006), or even during subclinical infection.…”
Section: Introductionsupporting
confidence: 69%
See 2 more Smart Citations
“…The potential for applying this approach for the detection and surveillance of FMDV has been identified in previous studies. For example, detection of FMDV RNA has been demonstrated at a dilution of up to 10 −7 , and assuming a negligible reduction in milk yield, it could theoretically be possible to identify one acutely infected milking cow in a herd of up to 1,000 using pooled milk sampling (Armson et al, 2018). Additionally, simulation modelling (Garner et al, 2016;Kompas et al, 2017;Thurmond & Perez, 2006) suggested pooled milk could be a useful tool in enhancing a surveillance system for FMD and considered for regional FMD surveillance.…”
Section: Introductionmentioning
confidence: 99%